2017
DOI: 10.12783/dtssehs/ermm2017/14671
|View full text |Cite
|
Sign up to set email alerts
|

Innovative Vocational Didactics Aimed at the Preparation of Staff According to Industry 4.0 and Europe 2020

Abstract: Abstract. The article presents the e-support methods for vocational learning process at three advancement levels, which can be useful for the preparation of staff according to Industry 4.0 concept and Europe 2020 Strategy. The authors present the application of the animation programmes, which are supportive for learning of CNC programming. They compare the way of learning with the use of real panels for the operator, which are the parts of an individual machine and the animation programme. In the article the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…We also address the issue of the tendency to use artificial intelligence resources and software technologies in the training universe. We concluded that such tools facilitate and Kowalik and Rusyn (2017), Lee and Kim (2015), Maity (2019), Training management software…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…We also address the issue of the tendency to use artificial intelligence resources and software technologies in the training universe. We concluded that such tools facilitate and Kowalik and Rusyn (2017), Lee and Kim (2015), Maity (2019), Training management software…”
Section: Discussionmentioning
confidence: 92%
“…However, the attention of the participants can be distracted by having animation that is not directly relevant to the training tasks, which can even result in unsatisfactory learning results. It is crucial to monitor whether the content of the training systems is closely related to the users' professional tasks (Kowalik and Rusyn, 2017;Maity, 2019). The e-learning modality allows the preparation of a virtual collaborative environment for the sake of easy and agile knowledge sharing.…”
Section: E-learning Training In Work Corporationsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the attention of the participants can be distracted by having animation that is not directly relevant to the training tasks, which can even result in unsatisfactory learning results. It is crucial to monitor whether the content of the training systems is closely related to the users’ professional tasks (Kowalik and Rusyn, 2017; Maity, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the advantages in obtaining results, the interactive nature of such teaching methods provides an intuitive and pleasant learning environment and interaction with a virtual laboratory [4]. The articles [5,6] present the e-support methods for vocational learning process at three advancement levels, which can be useful for the preparation of staff according to Industry 4.0 concept and Europe 2020 Strategy. The authors present the application of the animation programmes, which are supportive for learning of CNC programming.…”
Section: Introductionmentioning
confidence: 99%